0847 Associations between Objective Afternoon and Evening Physical Activity and Objective Sleep in Fibromyalgia. (12th April 2019) - McGovney, Kevin D; Curtis, Ashley F; McCann, Dillon; McCrae, Christina S
Abstract: Introduction: Patients with fibromyalgia (FM) suffer from chronic widespread pain which limits their physical activity, and is associated with disturbed sleep. However, the relationship between physical activity, pain level, and nighttime sleep is unclear. This study examined whether objectively measured activity levels (via actigraphy) and pain intensity are associated with actigraphically measured sleep. Methods: Adults with FM (n=160, Mage=52, SD=12, 93% female) completed 14 days of actigraphy. Activity levels (i.e., magnitude of wrist motion captured per 30 second epoch) were recorded, and average afternoon/evening activity for intervals 12:00-15:00, 15:00-18:00, and 18:00-21:00 was computed, removing days in which participants slept during these periods. Multiple linear regressions examined whether afternoon/evening activity, pain, or their interaction, predicted actigraphically measured sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), total wake time (TWT), early morning snooze time, and sleep efficiency (SE), controlling for age, body mass index, and usage of sleep or pain medication. Results: Greater evening activity from 18:00-21:00 was independently associated with lower SE ( B = -.01, p=.02) and higher TWT ( B =.06, p=.03). Greater pain intensity was independently associated with lower SE ( B = -.06, p=.03). Activity from 12:00-15:00 and 15:00-18:00 was not significantly associated with sleep outcomes. Conclusion: Results suggest that in FM, increased evening physical activity, regardless of pain level, may exacerbate objective sleep disturbance. It is likely that higher evening activity increases pre-bedtime arousal, and leads to more fragmented sleep. Reducing evening activity levels may help promote better sleep quality in FM. Support (If Any): NIAMS (R01AR055160/R01AR005160-S1;P1, McCrae). Data collected at the University of Florida (Clinical Trial-NCT02001077;PI, McCrae).